Cytokeratin‐based assessment of tumour budding in colorectal cancer: analysis in stage II patients and prospective diagnostic experience. (July 2017) - Koelzer, Viktor H; Assarzadegan, Naziheh; Dawson, Heather; Mitrovic, Bojana; Grin, Andrea; Messenger, David E; Kirsch, Richard; Riddell, Robert H; Lugli, Alessandro; Zlobec, Inti
Abstract: Tumour budding in colorectal cancer is an important prognostic factor. A recent consensus conference elaborated recommendations and key issues for future studies, among those the use of pan‐cytokeratin stains, especially in stage II patients. We report the first prospective diagnostic experience using pan‐cytokeratin for tumour budding assessment. Moreover, we evaluate tumour budding using pan‐cytokeratin stains and disease‐free survival (DFS) in stage II patients. To this end, tumour budding on pan‐cytokeratin‐stained sections was evaluated by counting the number of tumour buds in 10 high‐power fields (0.238 mm 2 ), then categorizing counts as low/high‐grade at a cut‐off of 10 buds, in two cohorts. Cohort 1: prospective setting with 236 unselected primary resected colorectal cancers analysed by 17 pathologists during diagnostic routine. Cohort 2: retrospective cohort of 150 stage II patients with information on DFS. In prospective analysis of cohort 1, tumour budding counts correlated with advanced pT, lymph node metastasis, lymphovascular invasion, perineural invasion (all p  < 0.0001), and distant metastasis ( p  = 0.0128). In cohort 2, tumour budding was an independent predictor of worse DFS using counts [ p  = 0.037, HR (95% CI): 1.007 (1.0–1.014)] and the low‐grade/high‐grade scoring approach [ p  = 0.02; HR (95% CI): 3.04 (1.2–7.77), 90.7 versus 73%, respectively]. In conclusion, tumour budding assessed on pan‐cytokeratin slides is feasible in a large pathology institute and leads to expected associations with clinicopathological features. Additionally, it is an independent predictor of poor prognosis in stage II patients and should be considered for risk stratification in future clinical studies.